Petualangan seru mengenal 32 kapal laut menakjubkan : termewah-terbesar-tercanggih / M. Lukman Hakiem; penyunting, Tin Zulaeha, Rini Yuliana; ilustrator, Salman Abdul Aziz - LUKMAN HAKIEM, M.; Tin Zulaeha; Rini Yuliana; Salman Abdul Aziz (Visi Mandiri, 2015)
112 hlm. : ilus. ; 24 cm.